HUBUNGAN PENGETAHUAN DAN PERSEPSI AKSEPTOR KB DENGAN PEMILIHAN KONTRASEPSI IUD PASCA IKUTAN SECTIO CAESAREA DI RSU SRIKANDI IBI JEMBER - Nur Baitillah, Sekar Wahyu; Hikmawati, Nova; Lestari, Dwi Anggun (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
The rate of population growth in Indonesia is increasing and is becoming a serious problem. One of the activities that can be carried out is to promote long-term effective contraceptive methods. Intrauterine Contraception Device (IUD) is a method that is widely used in family planning programs in Indonesia and after Sectio Caesarea is more practical to use. This study aims to determine the relationship between knowledge and perceptions of family planning acceptors and the choice of IUD contraception after participating in a caesarean section at Srikandi General Hospital IBI Jember. The research design uses correlational analysis with cross sectional research. The study population was family planning acceptors who chose IUD contraception after having a caesarean section at Srikandi IBI Hospital Jember, from January to December 2022, with a total of 987 post-cesarean patients: 12 = 82 respondents. This sample uses non-random sampling (non-probability): accidental sampling. Data were collected using a questionnaire and analyzed using a gamma correlation test. The results showed that from 82 respondents to family planning acceptors by filling out a questionnaire and calculating the data using the gamma test, the results obtained were p-value = 0.212 from the knowledge of family planning acceptors and p-value = 6.212 from the perception of family planning acceptors where the p-value ≥ α (0, 05). It was concluded there was no relationship between the knowledge and perceptions of family planning acceptors and the choice of IUD contraception after attending a caesarean section. This research can be used as a reference for similar research with a larger sample size so that the results are more representative to be generalized to other researchers.